Electrostatic origin of the red solvatochromic shift of DFHBDI in RNA spinach - Bose, Samik; Chakrabarty, Suman; Ghosh, Debashree (Journal of Physical Chemistry B, 2017)
Interactions with the environment tune the spectral properties of biological chromophores, e.g., fluorescent proteins. Understanding the relative contribution of the various types of noncovalent interactions in the spectral shifts can provide rational design principles toward developing new fluorescent probes. In this work, we investigate the origin of the red shift in the absorption spectra of the difluoro hydroxybenzylidene dimethyl imidazolinone (DFHBDI) chromophore in RNA spinach as compared to the aqueous solution. We systematically decompose the effects of various components of interactions, namely, stacking, hydrogen bonding, and long-range electrostatics, in order to elucidate the relative role of these interactions in the observed spectral behavior. We find that the absorption peak of DFHBDI is red-shifted by similar to 0.35 eV in RNA relative to the aqueous solution. Earlier proposals from Huang and co-workers have implicated the stacking interactions between DFHBDI and nucleic acid bases to be the driving force behind the observed red shift. In contrast, our findings reveal that the long-range electrostatic interactions between DFHBDI and negatively charged RNA. make the most significant contribution. Moreover, we notice that the opposing electrostatic fields due to the RNA backbone and the polarized water molecules around the RNA give rise to the resultant red shift. Our results emphasize the effect of strong heterogeneity in the various environmental factors that might be competing with each other.